2018
DOI: 10.1021/acsomega.8b01800
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characteristics, Population Analysis, and Binding Energies of [An(NO3)]2+(with An = Ac to Lr)

Abstract: Efficient predictive capabilities are essential for the actinide series since regulatory constraints for radioactive work, associated costs needed for specialized facilities, and the short half-lives of many actinides present great challenges in laboratory settings. Improved predictive accuracy is advantageous for numerous applications including the optimization and design of separation agents for nuclear fuel and waste. One limitation of calculations in support of these applications is that the large variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 85 publications
0
22
0
Order By: Relevance
“…4050 A previous study of [An(NO 3 )] 2+ structures established that utilizing the 6-31G*, cc-pVDZ, 6-311++G**, cc-pVTZ, and cc-pVQZ basis set for non-An atoms, the Stuttgart RSC 1997 ECP and associated basis set for the actinides include all of the basis functions in the basis set, while changing the functional (LDA, TPSS, B3LYP, PBE0, and B972) predicted structures with an An–O distance of less than 0.03 Å and an O–An–O angle difference of less than 1°. 36 In the current study, the strongly constrained and appropriately normed semilocal (SCAN) 51 density functional is also included as it had not yet been tested for actinides. The SCAN functional is utilized to analyze structural characteristics, population analysis, and differences in predicted Gibbs free energies of reaction of the uranyl compounds with relative to those predicted with B3LYP.…”
Section: Methodsmentioning
confidence: 99%
“…4050 A previous study of [An(NO 3 )] 2+ structures established that utilizing the 6-31G*, cc-pVDZ, 6-311++G**, cc-pVTZ, and cc-pVQZ basis set for non-An atoms, the Stuttgart RSC 1997 ECP and associated basis set for the actinides include all of the basis functions in the basis set, while changing the functional (LDA, TPSS, B3LYP, PBE0, and B972) predicted structures with an An–O distance of less than 0.03 Å and an O–An–O angle difference of less than 1°. 36 In the current study, the strongly constrained and appropriately normed semilocal (SCAN) 51 density functional is also included as it had not yet been tested for actinides. The SCAN functional is utilized to analyze structural characteristics, population analysis, and differences in predicted Gibbs free energies of reaction of the uranyl compounds with relative to those predicted with B3LYP.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study on [An(NO 3 )] 2+ compounds where An = Ac–Lr has also shown a ground state of an An III configuration instead of a An IV configuration for Fm, Md, and No atoms in the gas phase (but Fm IV and Md IV in the aqueous phase). 6…”
Section: Resultsmentioning
confidence: 99%
“…This approach was recently utilized in a similar study of [An(NO 3 )] 2+ compounds, for which the thermochemical corrections for the Gibbs free energies of reaction are obtained at each level of theory utilized for the geometry and vibrational frequency calculations. 6 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations